Advance healthcare directives: The emerging global trends and Shari’ah perspectives - Jahn Kassim, Puteri Nemie; Alias, Fadhlina (2017)
Advance Healthcare Directives emerged due to the enhancement of patient autonomy which ideals have been firmly embedded in the development of modern medical decision making. An advance healthcare directive is a document that seeks to preserve the patient’s right of self-determination by representing his values and wishes in the event he becomes incapacitated and no longer able to fully partake in the decision-making process. Particularly, when life sustaining measures are required in making end of life decisions, clear instructions embodied in the advance healthcare directives will serve as guidance to healthcare providers in respecting patient’s wishes, managing healthcare resources and reducing the likelihood of disputes with patient’s family members. Subsequently, the growth and popularity of these directives has led to the enactment of legislations by many countries in clarifying the legitimacy of such directives when employed in healthcare settings. The legal development of advance healthcare directives is seen to be more prominent in the United States, Australia and parts of Europe while countries in other jurisdictions may not specifically address the legal status of such directives in their legislations but treat them as being legally persuasive. Nevertheless, for Muslim patients, the use of advance healthcare directives to determine their health destiny must abide by the Shari’ah as the right and ability to make their own choices and decisions about medical care and treatment must be within the defined limitations of the Shari’ah. This paper seeks to discuss the legal development of advance healthcare directives in selected countries around the globe and the legitimacy of these directives from the Shari’ah perspectives.